Civic and Prosocial Decision-Making in Early Adolescents - Antonio Jamie Castro; Afiah Fozi; Chen-Yu Hung; Maureen Etoh; Christi Bergin (Youth)
This study investigated the everyday civic practices of early adolescents (ages 10–12) and explored their civic and prosocial decisions. Researchers conducted focus groups and interviews with elementary students about scenarios involving classmates in need of assistance. Participants were asked which civic and prosocial action they might take (or not take) in each situation and what factors influenced their decision-making. Findings revealed that participants assessed each situation, considering factors such as their ability to help, personal costs associated with helping, and their relationship with the target of the assistance. Other factors included participants’ emerging sense of self-identity and their ability to adopt the perspectives of others. Overall, this study suggested that early adolescents do engage in thoughtful deliberation given their everyday contexts and experiences.